International theory positivism and beyond - Smith, Steve 1952-; Booth, Ken 1943-; Zalewski, Marysia (Cambridge University Press, 1996)
This book provides a major review of the state of international theory. It is focused around the issue of whether the positivist phase of international theory is now over, or whether the subject remains mainly positivistic. Leading scholars analyse the traditional theoretical approaches in the discipline, then examine the issues and groups which are marginalised by mainstream theory, before turning to four important new developments in international theory (historical sociology, post-structuralism, feminism, and critical theory). The book concludes with five chapters which look at the future of the subject and the practice of international relations. This survey brings together key figures who have made leading contributions to the development of mainstream and alternative theory, and will be a valuable text for both students and scholars of international relations